الحضور الجزائري في الحروب العربية ضد الكيان الصهيوني 1948 - 1973 - جلالي، إكرام; بلبي، تهاني; رحال، مروة (University Of Eloued جامعة الوادي, 2024)
تميزت الجزائر بموقفها التضامني الحقيقي لنصرة الفلسطينيين قبل وبعد استقلالها 1962، فلم يتغير موقفها تجاه مساندتها للقضية وللعرب، فقبل الاستقلال ساند ممثلو الحركة الوطنية الجزائرية القضية الفلسطينية وذلك من خلال منشوراتهم وأعمالهم وشد بعضهم الرحال إلى فلسطين من اجل الجهاد، وبرز ذلك من خلال دور المتطوعين في حرب 1948، وبعد تحقيق استقلالها أبدت اهتماما ودعما كبيرين للقضية الفلسطينية ضد الكيان الصهيوني وأعلنت أنها مع فلسطين ظالمة أو مظلومة، فالجزائر في عهد الرئيس هواري بومدين عملت جاهدة على تهيئة الأجواء الملائمة للتعبئة التضامنية للجماهير العربية لأخذ دورها بمناصرة الشعب الفلسطيني وظهر ذلك من خلال دور الحكومة الجزائرية بإرسال جيشها إلى جبهات القتال في حربي 1967ـ1973وبتكثيف اتصالاتها مع القيادة السوفياتية للحصول على الأسلحة والمعدات العسكرية، وقد اعترفت شهادات اسرائيلية وأضفناها في هذه الدراسة بشجاعة الجزائريين وحجم عطائهم ودرجة تضحياتهم. Algeria was distinguished by its true solidarity position in support of the Palestinians before and after its independence in 1962. Its position towards supporting the cause and the Arabs did not change. Before independence, representatives of the Algerian national movement supported the Palestinian cause through their publications and actions, and some of them traveled to Palestine for the sake of jihad. This was evident through the role of volunteers in the 1948 war. After achieving its independence, it showed great interest and support for the Palestinian cause against the Zionist entity and declared that it was with Palestine, whether it was the oppressor or the oppressed. Algeria, during the era of President Houari Boumediene, worked hard to prepare the appropriate atmosphere for the solidarity mobilization of the Arab masses to take their role in supporting the Palestinian people. This was evident through the role of the Algerian government in sending its army to the battlefronts in the 1967-1973 wars and intensifying its contacts with the Soviet leadership to obtain weapons and military equipment. Israeli testimonies, which we have added to this study, acknowledged the courage of the Algerians, the extent of their giving, and the degree of their sacrifices.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: الحروب العربية – الإسرائيلية; القضية الفلسطينية; Arab-Israeli Wars; Palestinian Cause